THINKING OF FUTURE ENGINEER IN THE STUDY OF MATHEMATICS - Мойсеєнко, Л. А.; Шегда, Л. М. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
In this paper the authors justify the relevance of the study of mathematics to enhance the creative potential of future professionals in the technical field, which should ensure the development of innovative society, with opportunity to justify the formation of thinking student who is studying engineering, through the formation of high-quality mathematic thinking, considering the nature of mathematical thinking and distinguish its essential components that are part of the components of thinking engineer. Three mathematical thinking processes aimed at solving mathematical problems: the process of understanding the process of predicting, the process of testing, through the influence of which can achieve high quality of thinking of the future specialists addressing new technical problem.